2018
DOI: 10.1002/term.2660
|View full text |Cite
|
Sign up to set email alerts
|

Functional collagen conduits combined with human mesenchymal stem cells promote regeneration after sciatic nerve transection in dogs

Abstract: Numerous studies have focused on the development of novel and innovative approaches for the treatment of peripheral nerve injury using artificial nerve guide conduits. In this study, we attempted to bridge 3.5-cm defects of the sciatic nerve with a longitudinally oriented collagen conduit (LOCC) loaded with human umbilical cord mesenchymal stem cells (hUC-MSCs). The LOCC contains a bundle of longitudinally aligned collagenous fibres enclosed in a hollow collagen tube. Our previous studies showed that an LOCC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…Yao et al () showed that a longitudinally oriented collagen conduit combined with nerve growth factor (NGF) promotes functional and morphological nerve regeneration at the transection site of the injured sciatic nerve (a 35‐mm gap) after 9 months. It has also been shown that the joint application of a collagen conduit with various cells such as human umbilical cord mesenchymal stem cells (MSCs; Cui et al, ) and undifferentiated autologous adipose tissue‐derived stem cells (Klein, Vykoukal, Li, et al, ) can repair damaged nerves in terms of motor and sensory nerve conduction velocity values.…”
Section: Materials For Fabricating Nerve Conduitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yao et al () showed that a longitudinally oriented collagen conduit combined with nerve growth factor (NGF) promotes functional and morphological nerve regeneration at the transection site of the injured sciatic nerve (a 35‐mm gap) after 9 months. It has also been shown that the joint application of a collagen conduit with various cells such as human umbilical cord mesenchymal stem cells (MSCs; Cui et al, ) and undifferentiated autologous adipose tissue‐derived stem cells (Klein, Vykoukal, Li, et al, ) can repair damaged nerves in terms of motor and sensory nerve conduction velocity values.…”
Section: Materials For Fabricating Nerve Conduitsmentioning
confidence: 99%
“…In most studies, on the basis of their frequency of usage (high vs. low), animals such as rats (Labroo et al, ; Tao et al, ), mice (Lin, Shea, et al, ; Yokoi et al, ), rabbits (Chang et al, ; Hsu, Chan, Chiang, Chen, & Jiang, ), dogs (Cui et al, ; Yao et al, ), cats (Kitahara et al, ), sheep (Siemionow et al, ), and monkeys (Zhang et al, ) are used (Angius et al, ).…”
Section: Animal Model For Nerve Regeneration Studymentioning
confidence: 99%
“…Dai's lab also proved that functional collagen conduits with the fused proteins CBD‐CNTF and CBD‐bFGF facilitated nerve regeneration in a 3.5 cm facial nerve defect in a pig model (Cui et al, ; Lu et al, ). Longitudinally oriented collagen conduits (LOCCs) fused with human umbilical cord mesenchymal stem cells (hUC‐MSCs) can improve nerve regeneration in the 3.5 cm sciatic nerve defect model of dog (Cui et al, ). It is noteworthy that LOCCs plus CBD‐NGF also provide an environment that promotes sciatic nerve regeneration (Cui et al, ; Yao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinally oriented collagen conduits (LOCCs) fused with human umbilical cord mesenchymal stem cells (hUC‐MSCs) can improve nerve regeneration in the 3.5 cm sciatic nerve defect model of dog (Cui et al, ). It is noteworthy that LOCCs plus CBD‐NGF also provide an environment that promotes sciatic nerve regeneration (Cui et al, ; Yao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, a range of nerve guidance conduits (NGCs) based on the natural biology of nerve regeneration have been developed and studied in vivo and/or in vitro . In order to acquire ideal repair outcomes, a variety of strategies have been proposed to fabricate NGCs, which range from simple hollow tubes to filled tubes combined with intraluminal fillings, neurotrophic factors, or stem cells . At present, NGCs in hollow tubular structures made by collagen, non‐resorbable hydrogels, or resorbable biopolymers are approved by the Food and Drug Administration (FDA) …”
Section: Introductionmentioning
confidence: 99%